A Review on Ã¢â‚¬Å“Formulation, Development and Evaluation of Amisulpride Once Daily TabletÃ¢â‚¬Â - Upadhyat1, H. Bishnoi1, S. Savita1, S. Shailesh1*, O.P. Mahatama2, N. (Recent Research in Science and Technology, 2011)
The objective of the present study was to develop once-daily tablet of Amisulpride, a second generation antipsychotic, a substituted Benzamide. The tablets were prepared by the wet granulation method. Microcrystalline Cellulose, HydroxyPropylmethyl cellulose (HPMC), Talc, Magnesium Stearate, Iso Propyl alcohol, Xanthan Gum, Kollidone Cross Pobidone, Aerosil, Avesil 101, 112, 102, Sodium B i-car bonate, Poly vinylpyrollidone K-30, Carbopol with varying excipients Six bilayer formulations AM1 –AM6 were prepared by compressing both Instant Release ( IR) and Sustained Release ( SR) granules. The granules were evaluated for bulk density, tapped density, compressibility, and Hausner ratio and moisture content. The tablets AM1– AM6 were evaluated. The granules showed satisfactory flow properties. All the tablets formulations showed acceptable Pharmacotechnical properties and complied within specifications for tested parameters. The results of dissolution studies indicated that the formulation AM1 , AM2 and AM3 the release retardant use in combination of SR part & IR part, AM1 (80:20), AM2 (80:20)in combination of HPMC and poloxmer 188 and AM3 use is xanthane gum but process not fissile and dissolution was faster. Formulation AM6 exhibited satisfactory drug release; amisulpride OD Bi- layer 400 mg tablets dissolved more than 90% in 24 hours.